Challenges in urban property development against the background of changes in the real estate industry - Heeg, Susanne (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
Up to the 1980s, urban property development and management in Western Europe was structured by local conditions and actors. This has changed due to strengthened demand for office space, new forms of real estate financing and an increased market transparency as a consequence of political deregulation. At present, these changes go along with a mobilization of the urban property market and a shift from an use value perspective to an exchange value orientation. What kind of challenges and possibilities arise from these transformations for the urban property development? Does an increased importance of supraregional and shareholder value oriented property developers and investors imply a dependency of urban (property) development on mobile investments? In this article these questions will be answered by analyzing the effects of the reorganization of the real estate industry and the restructuring of urban policy.